Implementasi Program Edukasi Cinta, Bangga, Paham (CBP) Rupiah: Studi Empiris di Provinsi Jawa Timur - Nur Indah Sari; Hadyantari, Faizatu Almas (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study aims to analyze how the implementation of the Love, Proud, Understand (CBP) Rupiah education program in East Java affects the economy of East Java and analyzes the challenges that occur in the implementation of the CBP program in East Java. And, evaluate the implications of the CBP program in influencing the economy of East Java. Through the literature study analysis method with data and information collection based on the results of field visits related to the CBP socialization activities of Bank Indonesia East Java and through searches, such as scientific journals and other relevant documents. The results show that the CBP program has an important role in increasing awareness of the Rupiah and has a positive impact on the economy of East Java, especially on East Java's financial literacy. There are challenges faced by Bank Indonesia East Java, such as the widespread use of foreign currency in several sectors of the economy and limited access to financial services in remote areas. The conclusion of this study is the need for Bank Indonesia to make efforts to ensure that the CBP Rupiah program can reach all levels of society and have a broader impact on economic stability.